PENGARUH PENGADAAN BERAS DAN OPERASI PASAR TERHADAP HARGA BERAS DALAM NEGERI - Dioni Yurinda Rahmasuciana; Dwidjono Hadi Mulyo; Masyhuri MASY (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2015)
This research aimed to determine: (1) factors that affect domestic price of rice, (2) factors that affect the domestic rice availability, (3) domestic price stability of rice for 20 years (1993-2012), and (4) Influence of Market Operations domestic price stabilization. Descriptive analysis method was applied in this research. Secondary data were collected and analyzed with the sofware Eviews 4.0. Multiple linear regression analysis was applied by following the Ordinary Least Square (OLS) method, instead of statistical inference of mean, coefficient of variation (CV), and simple linear correlation analysis. Results of analyses showed that domestic price of rice is positively influenced by the dummy of Raskin and negatively affected by domestic rice procurement. Domestic rice availability is positively influenced by the harvested area and the disparity of price. Based on statistical inference test and the coefficient of variation, the domestic price of rice for the last 20 years (1993-2012) was not stable. Simple linear correlation analysis showed that market operations of Bulog affect positively toward the stabilization of domestic price of rice.